SGS-LTER ecosystem stress area: long-term dataset following nutrient enrichment stress on the Central Plains Experimental Range in Nunn, Colorado, USA, ARS study number 3 - Milchunas, Daniel G.; Lauenroth, William K. (Colorado State University. Libraries, 1974)
This data package was produced by researchers working on the Shortgrass Steppe Long Term Ecological Research (SGS-LTER) Project, administered at Colorado State University. Long-term datasets and background information (proposals, reports, photographs, etc.) on the SGS-LTER project are contained in a comprehensive project collection within the Repository (http://hdl.handle.net/10217/100254). The data table and associated metadata document, which is generated in Ecological Metadata Language, may be available through other repositories serving the ecological research community and represent components of the larger SGS-LTER project collection. The effect of plant community structure on nutrient cycling is fundamental to our understanding of ecosystem function. We examined the importance of plant species and plant cover (i.e. plant covered microsites vs bare soil) on nutrient cycling in shortgrass steppe of northeastern Colorado. We tested the effects of both plant species and cover on soils in an area of undisturbed shortgrass steppe and an area that had undergone nitrogen and water additions from 1971 to 1974, resulting in significant shifts in plant species composition.
The Short Grass Steppe site encompasses a large portion of the Colorado Piedmont Section of the western Great Plains. The extent is defined as the boundaries of the Central Plains Experimental Range (CPER). The CPER has a single ownership and landuse (livestock grazing). The PNG is characterized by a mosaic of ownership and land use. Ownership includes federal, state or private and land use consists of livestock grazing or row-crops. There are NGO conservation groups that exert influence over the area, particularly on federal lands.
Natural Resource Ecology Laboratory (NREL)
Shortgrass Steppe-Long Term Ecological Research (SGS-LTER)
Keywords: inorganic nutrients; populations; carbon; aboveground net primary production; disturbance; cover; density; fertilization; nitrogen; biomass; plants; grasslands